(untitled) (Experimental biology, 2009)
On the ground of field data the influence of sex, age and generative status of muriform rodents to the size of nematodes from suborder Oxyurata was established. The physiological peculiarities of sex and age groups of beasts and the generative status of females were considered as the determinants of potential food sources for the parasites (through the rates of substances and energy exchanges in the different mammals groups).